Pengaruh Penularan Transvenereal Virus Dengue Serotipe-3 Terhadap Viabilitas Telur Aedes aegypti Berdasarkan Variasi Lama Penyimpanan - Triwahyuni, Tusy; Maria Puji Lestari, Sri; Putri, Devita Febriani (Biospecies, 2020)
Abstract Infectious male Aedes aegypti mosquitoes can transmit dengue virus (DENV) to transvenereal non-infectious female mosquitoes. Infectious female mosquitoes will reduce DENV to the egg stage and propagate to the adult mosquito stage. Egg stage is a stage of viability / resistance of Dengue Hemorrhagic Fever (DHF) vector. The study aims to determine the effect of transvenereal transmission on egg viability resulting from parental Ae. aegyptifemale mosquitoe with DENV-3 infection, with variations in egg storage time. This type of experimental research with purposive sampling. Egg samples were obtained from the Ae. aegypti female parental mosquito detected positive DENV-3 by PCR testing. Egg samples were stored for 14, 30, 60 and 120 days. Analysis to determine differences in viability in eggs derived from infectious female mosquitoes compared to controls using an independent T-test. Analysis to determine the viability of eggs derived from parental infectious female mosquitoes based on variations in storage time using ANOVA. The results of the study stated that there was no significant difference (P = 0.794) between the average eggs that succeeded in becoming imago (viable eggs) derived from parental infectious female mosquitoes compared to controls. The analysis also stated that there was no significant difference (P = 0.18) between the average viable eggs derived from parental infectious female mosquitoes both storage duration for 14, 30, 60, or 90 days. Keywords: Aedes aegypti, dengue serotype 3, storage time, transvenereal transmission, egg viability.